2008
DOI: 10.1007/s11426-008-0109-1
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of magnetic chitosan microspheres and its applications in wastewater treatment

Abstract: The methods of preparation of magnetic chitosan microspheres have been introduced. In addition, their applications in the wastewater treatment, based on different kinds of wastewater, have been reviewed, and their mechanisms have been discussed. magnetic chitosan microspheres, preparation, applications in wastewater treatment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…It is reported that chitosan could carry out effi cient removal of metal ions and humic acids, and act as a good absorbent to absorb impurities present in wastewater (Yang et al 2009 ). In the cosmetics industry, chitosan is used in several applications, including hair care, skin care, and oral care (Dutta et al 2004 ).…”
Section: Other Applicationsmentioning
confidence: 99%
“…It is reported that chitosan could carry out effi cient removal of metal ions and humic acids, and act as a good absorbent to absorb impurities present in wastewater (Yang et al 2009 ). In the cosmetics industry, chitosan is used in several applications, including hair care, skin care, and oral care (Dutta et al 2004 ).…”
Section: Other Applicationsmentioning
confidence: 99%
“…Besides, secondary pollutions may occur in effluents. In recent years, growing attention has been paid to adsorption for its high efficiency in low concentration sewages, relatively simple process and reusability [7]. Among the adsorbents, natural polymers are considered as outstanding candidates since they are nontoxic, reproducible, inexhaustible, biodegradable and environment-friendly [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…With the aid of magnetic force, magnetic matters can be separated from the water efficiently regardless of its size. MST also bear the characteristics of large-capacity, high-efficiency, and small scale [7]. Some techniques of the water treatment based on MST have already been put into practical application, such as the MIEX ® technique developed by Orica Watercare and two leading Australian research organizations, which exhibits extraordinary effects in the removal of heavy metal ions, sulfate, nitrate and DOC from waste water [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan has a pore structure, and there are active functional groups of hydroxyl and amino in its molecules. Chitosan also has strong coordination ability to phenols, acids and heavy metals (Bailey et al 1999;Kumar 2000;Yang et al 2008;Imran et al 2012). However, due to chitosan's shortcomings of easy loss, low mechanical strength and lack of regeneration ability, the application of chitosan is quite restricted (Zhen et al 2011).…”
Section: Introductionmentioning
confidence: 99%